Influence of nickel addition and casting modulus on the properties of hypo-eutectic ductile cast iron - Colin-García E.; Cruz-Ramírez A.; Reyes-Castellanos G.; Romero-Serrano J.A.; Sánchez-Alvarado R.G.; Hernández-Chávez M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The effect of the casting modulus on the distribution and features of graphite in hypo-eutectic ductile iron unalloyed and alloyed with nickel (0.88 wt %) was studied. The cooling rate of the casting plates of 25.4, 12.7 and 8.5 mm in thickness with a casting modulus of 6.87, 4.46 and 3.31 mm, respectively promotes several microstructural changes, such as cementite precipitation and a noticeable nodule count increment. The nickel addition suppressed the cementite formation and improved the nodule count and nodularity for the three casting modulus evaluated. The nickel addition increased the nodule count in 69, 67 and 128 % for the modulus of 3.31, 4.46 and 6.87 mm, respectively, regarding the unalloyed ductile iron. It was found that the biggest casting modulus produced the biggest nodules with the lowest nodule count for both ductile cast irons. Further to the improvements in the graphite features, the nickel addition allowed to keep almost constant the yield and tensile strength ratio for the different casting modulus.